Characterizing the role and regulation of growth arrest specific FABP4 in chicken embryo fibroblasts - Donders, Jordan (My University, 2020)
Conditions which promote reversible growth arrest, such as hypoxia and high cell density, lead to activation of a diverse network of proteins known as growth arrest specific (GAS) genes. Fatty acid binding protein 4 (FABP4), a lipid chaperone involved in the regulation of metabolic and inflammatory responses, has been shown to be part of the GAS program. While the induction of FABP4 in oxygen-deprived environments is well characterized, its functionality and regulation in such conditions remains unclear. In this study, we describe how mis-expression of FABP4 affects cell viability and survival within low oxygen conditions. Loss of FABP4 using shRNA was shown to be associated with a significant increase in oxidative stress and lipid peroxidation, a reduction in lipid droplet formation and a greater incidence of apoptosis. Hypoxia-mediated expression of FABP4 was also found to be positively correlated with cellular levels of C/EBP-beta, an essential activator of p20K in quiescence. FABP4 and p20K are both lipocalins that have been shown to share similar induction patterns and ability to assist in the maintenance of lipid trafficking in cellular stress circumstances. Unexpectedly, the depletion of FABP4 or p20K results in loss of the other in limited oxygen concentrations. This occurs independently of disruption to the broad GAS gene program, suggesting the two proteins may be co-regulated in a shared hypoxic-signalling pathway. C/EBP-beta appears to be the transcriptional activator shared by FABP4 and p20K in quiescence, and the three may be part of an intricate system to sense and respond to reactive oxygen species and lipid radicals. However, the forced expression of either FABP4 or p20K when the other is repressed only moderately restores cell survival through alleviating oxidative stress, indicating the two are both necessary for optimal response to hypoxia. In all, these studies suggest that analogous to the p20K lipocalin, FABP4 plays a critical role in lipid homeostasis and cell survival in conditions of limited oxygen concentrations, and its stimulation is dependent on C/EBP-beta activity.
Keywords: quiescence; reversible growth arrest; fatty acid binding protein 4 (FABP4); AP2; P20K; Lipocalin; chicken embryo fibroblast (CEF); Growth arrest specific gene (GAS); C/EBP-beta; oxidative stress; hypoxia; lipid peroxidation; membrane stress response; lipid damage response; reactive oxygen species; contact inhibition